Efficient linear discriminant analysis with locality preserving for face recognition - Shu, Xin; Gao, Yao; Lu, Hongtao (Pattern recognition, 2012)
Linear discriminant analysis (LDA) is one of the most popular techniques for extracting features in face recognition. LDA captures the global geometric structure. However, local geometric structure has recently been shown to be effective for face recognition. In this paper, we propose a novel feature extraction algorithm which integrates both global and local geometric structures. We first cast LDA as a least square problem based on the spectral regression, then regularization technique is used to model the global and local geometric structures. Furthermore, we impose penalty on parameters to tackle the singularity problem and design an efficient model selection algorithm to choose the optimal tuning parameter which balances the tradeoff between the global and local structures. Experimental results on four well-known face data sets show that the proposed integration framework is competitive with traditional face recognition algorithms, which use either global or local structure only. ► We proposed a regularized least squares LDA which integrates both the global and local structures for face recognition. ► The formulation of regularized least squares LDA is based on spectral regression. ► The local structure is modeled via a regularization term defined by the graph Laplacian. ► We design an efficient algorithm for the estimation of the optimal tuning parameter.